2020
DOI: 10.3390/ijerph17155555
|View full text |Cite
|
Sign up to set email alerts
|

Imbalances in the Study of the Relationship between Leisure and Self-Esteem: A Systematic Review

Abstract: This systematic review offers a comprehensive examination of the relationship between leisure and self-esteem. The different perspectives were analyzed according to a framework that includes the different approaches for defining and measuring leisure, and a similar one was proposed for self-esteem. Articles indexed in the Web of Science (WoS) up to the end of 2018 were reviewed, specifically those that contained the keywords “leisure”, “self-esteem” or “self esteem” anywhere in the manuscript. Articles that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…(2) Structural validity Through exploratory factor analysis, it was found that the structure of the scale was in line with previous expectations, ensuring that the scale had good structural validity. In this study, the KMO coefficient is 0.902, and the probability value of the Barrett sphericity test is 0.000, which is less than 0.01, indicating that the correlation matrix can be used for factor analysis [14]. Four factors were extracted using principal component analysis, with a cumulative variance contribution rate of 61.497%.…”
Section: Test Validitymentioning
confidence: 82%
“…(2) Structural validity Through exploratory factor analysis, it was found that the structure of the scale was in line with previous expectations, ensuring that the scale had good structural validity. In this study, the KMO coefficient is 0.902, and the probability value of the Barrett sphericity test is 0.000, which is less than 0.01, indicating that the correlation matrix can be used for factor analysis [14]. Four factors were extracted using principal component analysis, with a cumulative variance contribution rate of 61.497%.…”
Section: Test Validitymentioning
confidence: 82%
“…Leisure is commonly defined as activities undertaken during one’s free time for pleasure and personal choice ( Bradley and Inglis, 2012 ), and it is a source of personal and social growth and development ( Alonso et al, 2019 ). This concept encompasses both an objective perspective, focusing on the activities themselves, the environments in which they occur, and the time periods allocated to them, and a subjective perspective, concerned with the meanings, experiences, and personal needs that these activities fulfill ( Codina and Freire, 2020 ). Measuring leisure involves two distinct approaches: the researcher’s analysis of activity records and the participant’s experiential assessment, which considers aspects like satisfaction and associated meaning ( Codina and Freire, 2020 ).…”
Section: Family Leisure and Adolescent Autonomy Developmentmentioning
confidence: 99%